2014
DOI: 10.1007/s10620-013-3019-9
|View full text |Cite
|
Sign up to set email alerts
|

Slow Pull Versus Suction in Endoscopic Ultrasound-Guided Fine-Needle Aspiration of Pancreatic Solid Masses

Abstract: The slow-pull technique was associated with less contamination with blood and can potentially increase the diagnostic yield compared with the suction technique in EUS-FNA of pancreatic solid masses, especially with a 25-gauge FNA needle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
126
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 158 publications
(130 citation statements)
references
References 22 publications
2
126
0
1
Order By: Relevance
“…There was no difference in the quality of aspirates between FNA with suction and the slow-pull technique when a 22-gauge needle was used. 12 As suggested by the cited studies, the use of suction may improve cellularity and the quality of aspirate, but at the cost of increased bloodiness and contamination. The increased bloodiness and contamination may lead to reduction in diagnostic accuracy, thereby negating any benefits of higher cellularity.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in the quality of aspirates between FNA with suction and the slow-pull technique when a 22-gauge needle was used. 12 As suggested by the cited studies, the use of suction may improve cellularity and the quality of aspirate, but at the cost of increased bloodiness and contamination. The increased bloodiness and contamination may lead to reduction in diagnostic accuracy, thereby negating any benefits of higher cellularity.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the pathologists selected in our study were dedicated to gastrointestinal diseases, therefore that we cannot predict if the high degree of reproducibility among them observed in our study can also be found among non-dedicated pathologists. Fifth, we did not utilize the so called "slow pull technique" that seems to gather better samples when a 25G needle is used [35]. However, this data was not yet available and the current evidence is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…8,17,18 Bang and colleagues reported high diagnostic yield using FNA needle without suction while others have shown that the slow-pull or “capillary suction” technique by slowly withdrawing the needle stylet while obtaining samples resulted in a higher yield. 19,20 Lee at al performed a randomized controlled trial on 81 patients with solid pancreas masses comparing cytologic features as well as diagnostic yield in samples obtained with and without suction. 9 Samples obtained with the use of 10 mL suction had higher diagnostic yield (72.8% vs. 58.6%, p = 0.001), cellularity (OR: 2.12, 95% CI: 1.3–3.3, p < 0.001), and also greater accuracy (82.4% vs. 72.1%, p < 0.001) compared to samples obtained without suction.…”
Section: Discussionmentioning
confidence: 99%